Mesoporous Silica Nanoparticles as Theranostic Antitumoral Nanomedicines - Alejandro Baeza; Maria Vallet-Regí (MDPI AG, 2020)
Nanoparticles have become a powerful tool in oncology not only as carrier of the highly toxic chemotherapeutic drugs but also as imaging contrast agents that provide valuable information about the state of the disease and its progression. The enhanced permeation and retention effect for loaded nanocarriers in tumors allow substantial improvement of selectivity and safety of anticancer nanomedicines. Additionally, the possibility to design stimuli-responsive nanocarriers able to release their payload in response to specific stimuli provide an excellent control on the administered dosage. The aim of this review is not to present a comprehensive revision of the different theranostic mesoporous silica nanoparticles (MSN) which have been published in the recent years but just to describe a few selected examples to offer a panoramic view to the reader about the suitability and effectiveness of these nanocarriers in the oncology field.